The Influence of Transformational Leadership and Job Satisfaction on Employee Performance in Ogan Komering Ilir Regency - Octavianti, Merryda; Mellita, Dina; Herdiansyah, ⁠M. Izman; Trisninawati (Yayasan Sinergi Kawula Muda, 2025)
This paper explores the factors that either hinder or support performance improvement among civil servants (PNS) in Ogan Komering Ilir Regency. The topic is vital due to the critical role of government employees in delivering effective and efficient public services, as well as the need for practical strategies to enhance organizational performance. The study investigates the challenges faced by local governments in improving employee performance, with the aim of identifying key factors and proposing actionable solutions. A quantitative approach was employed, using stratified random sampling to gather data from 378 civil servants via Likert scale-based questionnaires. The relationship between transformational leadership, job satisfaction, and employee performance were analyzed using SEM-PLS. The analysis revealed that transformational leadership significantly influences both job satisfaction and employee performance. Additionally, the results showed a strong correlation between these factors, underscoring key areas where leadership and satisfaction improvements could enhance performance. The study concludes that strengthening transformational leadership and job satisfaction can have a positive impact on employee performance. The findings provide practical implications for local government policymakers to implement targeted interventions aimed at boosting organizational efficiency. The key takeaway is that leadership development and job satisfaction are crucial to achieving higher performance in the public sector.